Desmoplastic melanoma. Issue 2 (27th November 2018) - Nicolson, Norman G; Han, Dale
Abstract : Desmoplastic melanoma (DM) is a rare melanoma variant that has unique biology and pathology compared with conventional melanoma (non‐DM). Importantly, DM is classified into pure and mixed histologic subtypes, which have been correlated with outcomes. Management of DM broadly mirrors that of non‐DM; however, there are unique considerations for DM that influence treatment approaches. This paper will provide a contemporary overview of this disease and will review the literature regarding the management of DM.